توظيف التكنولوجيات الحديثة في تحقيق أمن الموارد المائية: عرض تجارب عالمية - بن غيدة، سارة Bin Ghidah, Sarah; حركات، سعيدة (جامعة الشهيد حمه لخضر الوادي, 2020)
الماء عنصر حيوي وأساسي للحياة، فهو أساس التنمية الاقتصادية بشتى أنواعها، ومن أهم أولويات كافة الدول وهو ما نلاحظه من خلال سعي هذه الأخيرة إلى توظيف تقنيات حديثة للحفاظ عليه، وتنميته وترشيد استخدامه لتحقيق ما يسمى بالأمن المائي، فندرة المياه وغياب ثقافة ترشيدها من العوامل التي تهدد أمنها بصفة أو بأخرى. لذا فالهدف من هذه الورقة البحثية هو إبراز دور التكنولوجيات الحديثة في استدامة الأمن المائي، إذ استعرضت الدراسة أسباب ندرة الموارد المائية، ثم عموميات حول الأمن المائي، وأخيرا أبرزت الدراسة أهم مظاهر التكنولوجيا الحديثة في إرساء وتعزيز الأمن المائي من خلال عرض لبعض التجارب العالمية الناجحة في هذا المجال.
Water is a vital and essential component of life, as it is the basis of economic development of all kinds, and one of the most important priorities of all countries, which is what we observe through the endeavor of the latter to employ modern technologies to preserve, develop and rationalize its use to achieve what is called water security, the scarcity of water and the absence of a culture of rationalization of it. That threatens its security in one way or another. So the aim of this research paper is to highlight the role of modern technologies in the sustainability of water security, as the study reviewed the reasons for the scarcity of water resources, then generalities about water security, and finally the study highlighted the most important aspects of modern technology in establishing and enhancing water security through a presentation of some successful global experiences in this field.
Keywords: الموارد المائية -- الأمن المائى -- التكنولوجيا الحديثة -- التنمية الاقتصادية